A study of user participation across different delivery modes of a massive open online course. (2016) - Sinclair, Jane; Boyatt, Russell; Foss, Jonathan; Rocks, Claire
Massive open online courses (MOOCs) are offered by many universities, with hundreds of thousands of people worldwide having registered for one or more of the many available courses. Despite the potential that has been claimed for these courses to transform education, in practice the majority are deeply conservative in maintaining the educational status quo. Lacking innovative pedagogic foundation and with the need for approaches that scale, many courses rely heavily on very traditional methods such as mini-lectures and quizzes. In particular, learner support is proving to be insufficient for many participants. This paper reports results and experience from developing and presenting a MOOC which provides both 'traditional' and supported modes. Users can opt to study the course in the way familiar within most MOOCs (with peer support and limited tutor input) or to receive a high level of experienced tutor support. Having both modes run in parallel allows direct comparison between the experiences and achievements of the two groups. We present the motivation and objectives for the course, discuss results obtained and reflect on lessons learned in the process.